Design strategies in science centre - Baniyamin, Nurhaya; Abdul Rahim, Zaiton (Institute of Physics Publishing, 2019)
This study presents semiotics semantics theory as a possible standard for exploring the interrelations amid learning and the design of informal learning environments. The theoretical notions of classification (Bernstein, 1996), formality (Halliday, 1996), and framing (Bernstein, 1996) were sourced to explain the approach in selected exhibition galleries in Petrosains. Studies on the relationships between signs and symbols and what they represent, especially the relations between form and their reference in the physical world or the world of ideas, have been performed. Applying the semiotics semantics theory to the science centre settings has significant ability for expanding awareness of the role that exhibition plays in the visitor experience, and apprising the design strategies. The findings suggest that the representational modes do promote an investigative learning of science in pedagogical functioning.